Subdirect products of semirings - P. Mukhopadhyay (International Journal of Mathematics and Mathematical Sciences)
Bandelt and Petrich (1982) proved that an inversive semiring S is a subdirect product of a distributive lattice and a ring if and only if S satisfies certain conditions. The aim of this paper is to obtain a generalized version of this result. The main purpose of this paper however, is to investigate, what new necessary and sufficient conditions need we impose on an inversive semiring, so that, in its aforesaid representation as a subdirect product, the ring involved can be gradually enriched to a field. Finally, we provide a construction of full E-inversive semirings, which are subdirect products of a semilattice and a ring.